Effect of Stress on Ovarian Follicular Activity in Postpartum Sahiwal Cows during Summer Season - Singh, Raju Kumar; Awasthi, Manoj Kumar; Bhonsle, Dhirendra; Kaiser, Parveen (The Indian Journal of Animal Reproduction, 2024)
Present investigation was carried out to study the effect of heat stress on ovarian follicular activity in postpartum acyclic Sahiwal cows during summer seasonfrom April to June. Postpartum ovarian activity was monitored using trans-rectal ultrasound scanning on alternate days beginning between day 60 and 90 postpartum in Sahiwal cows (n=16) up to next 21 days. Daily maximum temperature and relative humidity was recorded and temperature-humidity index (THI) was calculated during study period. Four animals (25%) showed presence of dominant follicle (≥ 10 mm, cyclic) and remaining 12 animals (75%) were classified as acyclic (ovarian follicle < 10 mm diameter). Present study demonstrated that as the value of THI reduced, the mean follicular diameter proportionately increased and vice versa. Based on the findings of present study, it may be concluded that development of ovarian follicle is highly affected by THI value during summer season in Sahiwal cows and the reproductive performance of animal may be predicted using THI values.